2015
DOI: 10.1111/jace.13832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Glass Structure on Emission of Rare‐Earth‐Doped Borate Glasses

Abstract: A series of glasses composed of xB 2 O 3 -8Al 2 O 3 -(90 -x)Na 2 O-R 2 O 3 (x = 65, 70, 75, 80, 85; R = Dy 3+ , Tb 3+ , Sm 3+ ) were prepared through melt-quenching. Structural evolution was induced by varying the glass composition. Increasing the glass network former B 2 O 3 enhanced the luminescence of rare-earth ions, as observed in the emission spectra. The mechanism of the glass structural evolution was investigated by the NMR spectra analysis. The dispersant effect of the glass structure was believed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In the Eu 3+ ion case, the reduction of the B2O3 glass concentration can increase the luminescence intensity [2]. In another case, the addition of B2O3 decreases the BO4 unit and increases the number of BO3 units indicating that most of the BO4 units are converted to BO3 units [3]. The addition of R2O such as Na, Li or K improves the glass structure, including BO4 or NBO formation.…”
Section: Introductionmentioning
confidence: 99%
“…In the Eu 3+ ion case, the reduction of the B2O3 glass concentration can increase the luminescence intensity [2]. In another case, the addition of B2O3 decreases the BO4 unit and increases the number of BO3 units indicating that most of the BO4 units are converted to BO3 units [3]. The addition of R2O such as Na, Li or K improves the glass structure, including BO4 or NBO formation.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we investigate a series of Ce 3+ ‐, Ho 3+ ‐, and Sm 3+ ‐doped oxyfluoride silicate glasses. To generate the white light luminescence, Ce 3+ ions with a broad emission band in the blue region and Sm 3+ ions possessing three emission peaks at 560 (green), 596 (orange), and 642 nm (red) are introduced into the glass matrices. Comparing to the orange and red emissions of Sm 3+ as well as the blue emission of Ce 3+ , the green emission of Sm 3+ ions is too weak to make the white light with good quality in the Ce 3+ /Sm 3+ co‐doped glasses.…”
Section: Introductionmentioning
confidence: 99%
“…8 By controlling the borate speciation, a variety of physical properties of glass can be engineered of density, viscosity, refractive index, chemical durability, atom diffusion, ionic and thermal conductivities, thermal expansion coefficient, microhardness, biocompatibility, and aggregation/chemical state of dopants etc. 3,[9][10][11][12][13][14] For examples, recently, a record-high resistance to crack damage was reported in a lithium aluminoborate glass, owing to the self-adaptive nature of the glass network through the transformation of nonring [BØ 3 ] to [BØ 4 ] − during densification. 3 Trigonal boron was found to be more favorable than tetrahedral one for promoting fast and effective ion exchange.…”
mentioning
confidence: 99%
“…The shielding effect of [BØ 4 ] − , viz., protecting multivalent metal ions against oxidation, was also utilized to maintain lower valent Eu 2+ in borate glasses. 10 Jiao et al 11 reported that the formation of nonring trigonal boron helps avoid rare earth (RE) ions (eg, Dy 3+ , Tb 3+ , Sm 3+ ) clustering in glass, and leads to enhanced photoluminescence (PL). The planar [BØ 3 ] was assumed to ease the movement of Pb 2+ and Se 2− ions and thus facilitated the growth of PbSe quantum dots in glass.…”
mentioning
confidence: 99%
See 1 more Smart Citation